Analisis Sistem Tanggap Darurat Dalam Upaya Penanggulangan Kebakaran di Tempat Kerja - Putri Pasaribu, Natasha Melfisyaira; Oktavia, Ratih; Khairunnisa, Tia Zahra; Hasibuan, Abdurrozzaq (JPM MOCCI : Jurnal Pengabdian Masyarakat Ekonomi, Sosial Sains dan Sosial Humaniora, Koperasi, dan Kewirausahaan, 2024)
Fire is a fire that cannot be controlled and can cause enormous material and emotional losses According to the Regulation of the Minister of Public Works and Public Housing of the Republic of Indonesia Number 26 of 2008, fire hazard refers to the potential and degree of exposure to fire, smoke and gas. Fires are caused by the presence of three main elements: fuel, heat source, and oxygen. This is known as the fire triangle theory. A fire protection plan is an important document that contains detailed instructions on how to respond if a building fire occurs. Occupational safety and health protection is an important preventive measure to reduce the danger of fire this research aims to analyze the fire protection systems installed in workplaces and assess their effectiveness. The research method used is descriptive and qualitative Based on the results of several studies, although various companies' fire protection systems are implemented by applicable regulations and standards, aspects such as control of fire fighting equipment and emergency response intensity still need to be optimized. Simulation To reduce the risk of fire, it is important to ensure that the fire protection system complies with applicable regulations.